Risk factors and nomogram model for recurrence of benign paroxysmal positional vertigo in postmenopausal women: a multicenter cross-sectional study - Qing-Chun Pan; Bei Li; Kai Zou (Frontiers in Neurology)
ObjectiveTo explore the risk factors for recurrent benign paroxysmal positional vertigo (BPPV) in postmenopausal women within 1 year of canalith repositioning procedure (CRP), and develops a risk model based on serum 25-hydroxyvitamin D (25(OH)D), estradiol, and calcium levels to provide early identification of high-risk groups and guide prevention and treatment strategies.MethodsData from postmenopausal women with BPPV, diagnosed and successfully treated with CRP at five hospitals in Sichuan Province between January 2019 and January 2024, were retrospectively analyzed. Participants were divided into BPPV validation and training sets in a 3:7 ratio. Clinical data were categorized into recurrence and non-recurrence subgroups based on whether BPPV recurred after treatment. LASSO regression identified factors influencing recurrence within 1 year after CRP, and multivariate logistic regression (MLR) analysis was used to develop a risk nomogram prediction model (NPM).ResultsA total of 490 patients were enrolled, with 147 in the validation set and 343 in the training sets. Among them, 151 patients (30.82%) experienced recurrenced, including 58 (30.61%) in the validation set and 106 (30.90%) in the training sets. LASSO and MLR analyses identified migraine (OR = 2.208, 95% CI = 1.278–3.817), serum calcium (OR = 0.601, 95% CI = 0.447–0.81), 25(OH)D (OR = 0.785, 95% CI = 0.713–0.864), and serum estradiol (OR = 0.820, 95% CI = 0.752–0.894) as significant factors influencing recurrence within 1 year after CRP treatment in postmenopausal women with BPPV.ConclusionThe recurrence rate of BPPV within 1 year after CRP treatment in postmenopausal women is high. Migraine, 25(OH)D, calcium, and estradiol are associated with recurrence. The risk prediction model, developed using these factors, demonstrates good discrimination and calibration. It effectively predicts the recurrence risk within 1 year after successful CRP treatment, offering practical clinical value.